2003
DOI: 10.1002/mabi.200350014
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Graft Copolymers as Carriers for Delivery of Antisense‐Oligonucleotides

Abstract: Self‐assembling systems based on ionic complexes of DNA fragments (36 base pairs), bcl‐2 antisense oligonucleotides (octadecamer), oligophosphates (25 phosphate groups) or acrylic oligomers (18 groups of phosphonic acid) with poly(L‐lysine) (PLL) ($\overline M _{\rm w}$ = 130 000 and 88 000) grafted with short poly[N‐(2‐hydroxypropyl)methacrylamide] (PHPMA) chains ($\overline M _{\rm n}$ = 4 300 or 8 600) were studied by static and dynamic light scattering methods as systems suitable for gene therapy applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Typically, D-C3Ms exhibit lower critical ionic strengths, I cr , and aggregation numbers, P agg , and higher critical micellization concentrations (CMCs) than their S-C3Ms counterparts. With increasing copolymer block length ratio, N corona /N core , S-C3M molecular weight, M w , P agg , and hydrodynamic radius, R h are found to decrease [27,60,63,71,89,90,203,211,245]. For a given N corona , micellar size increases with increasing N core , [18,90,92,187,222] while for a given N core , R h increases with increasing N corona [118,119,125].…”
Section: Comicellization With Synthetic (Co)polymersmentioning
confidence: 81%
See 1 more Smart Citation
“…Typically, D-C3Ms exhibit lower critical ionic strengths, I cr , and aggregation numbers, P agg , and higher critical micellization concentrations (CMCs) than their S-C3Ms counterparts. With increasing copolymer block length ratio, N corona /N core , S-C3M molecular weight, M w , P agg , and hydrodynamic radius, R h are found to decrease [27,60,63,71,89,90,203,211,245]. For a given N corona , micellar size increases with increasing N core , [18,90,92,187,222] while for a given N core , R h increases with increasing N corona [118,119,125].…”
Section: Comicellization With Synthetic (Co)polymersmentioning
confidence: 81%
“…In the intracellular environment, one may envision exchange reactions with mRNA, sulphated sugars, and nuclear chromatin, while in the extracellular medium, one may think of exchange with blood serum proteins, such as BSA. Several studies found DNA-incorporation to be (at least partially) reversible as PAsp could replace DNA in DNA/PEO-b-PLys C3Ms [248], PSS could (at least partially) replace DNA from C3Ms of DNA/PHPMA-g-PLys, [71] and PVS could partially replace DNA from C3Ms of DNA/PEO-b-PLys [204]. Oupicky et al, found that while PSS could, albumin could not release DNA from DNA/PHPMA-b-PTMAEMA micelles in the presence of salt [207].…”
Section: Comicellization With Synthetic (Co)polymersmentioning
confidence: 99%
“…Another reasonable explanation is that as more polymer is added to go from low N/P ratios to ratios closer to neutrality, the number of micelles increases, leading to higher scattering intensity. Alternatively, Dautzenberg et al have shown that the maximum in scattering intensity was associated with an increase in the mean polymer weight fraction of individual PICMs, reflecting an increase in the density or compactness of the micelles (37). It is therefore suggested that the increase in scattering intensity observed here at the N/P ratio of 1.5 is due to the combined effects of the number of micellar assemblies and of hydrophobicity on size and density of the micelles.…”
Section: Colloidal Propertiesmentioning
confidence: 87%
“…[20,21] Changes of c and n due to a surface coating of PECs were calculated by a procedure given in our previous papers. [22,23] We have determined the refractive index increment of polymer 14, n ¼ 0.138 mL Á g À1 . Since the structure of the coating polymer contains almost 90 wt.-% of PEG chains it is not surprising that this value is very close to that of neat PEG, n ¼ 0.135 mL Á g À1 .…”
Section: Surface Modification Of Pll/dna Complex With Polymer 15mentioning
confidence: 99%